2015
DOI: 10.1017/jns.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Differences between men and women in dietary intakes and metabolic profile in response to a 12-week nutritional intervention promoting the Mediterranean diet

Abstract: Few studies have compared men and women in response to nutritional interventions but none has assessed differences between men and women in the response to a nutritional intervention programme based on the self-determination theory (SDT) and using the Mediterranean diet (MedDiet) as a model of healthy eating, in a context of CVD prevention and within a non-Mediterranean population. The present study aimed to document differences between men and women in changes in dietary, anthropometric and metabolic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(55 reference statements)
3
19
0
1
Order By: Relevance
“…The sex-specific associations between industrial TFAs, conjugated linoleic acids and PC risk that we found in our analysis may reflect differences in hormone levels and dietary patterns between men and women. 31 However, the sample size may have been insufficient to detect robust statistical heterogeneity between genders and it is also possible that the results are due to chance. Replication in study populations with a larger number of cases or a wider intake of these FAs are required to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sex-specific associations between industrial TFAs, conjugated linoleic acids and PC risk that we found in our analysis may reflect differences in hormone levels and dietary patterns between men and women. 31 However, the sample size may have been insufficient to detect robust statistical heterogeneity between genders and it is also possible that the results are due to chance. Replication in study populations with a larger number of cases or a wider intake of these FAs are required to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Tests for linear trend were performed by entering the median value of each tertile as continuous term in the multivariable models. Analyses were also stratified by sex because of differences in metabolic profile between men and women in response to nutritional interventions . We used a chi‐squared statistic to test for heterogeneity between log transformed percentiles of plasma phospholipid FAs by sex comparing the deviations of logistic beta‐coefficients observed in each subgroup relative to the overall beta‐coefficient .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our results were adjusted to age and use of antihypertensive medications only, other confounding factors such as socioeconomic, BMI, and other behavioral factors may explain the difference found between men and women. Some data suggest that sex‐related characteristics such as the level of sex hormones may interact with the results . Future research is needed to clarify the long‐term role of the LMD on BP prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Lassen et al (2004) explores several strategies to successfully increase fruit and vegetable intake that might also be expected to reduce the amount of meat served in cafeteria settings, such as seeking inspiration from cuisines that tend to be plantbased or offering cooked vegetables as well as salads, since cooked vegetables are easier to digest in large portions. Researchers have also encouraged adoption of the Mediterranean diet for its health benefits (Leblanc et al 2015) since this diet has been shown to have a lower carbon footprint than typical western diets (van Dooren et al 2014). Other studies have found that participants who received statements of dynamic norms (namely that a growing fraction of the population have begun to eat less meat) were more likely to purchase meatless lunches than participants in a static norm or a control group (Sparkman and Walton 2017).…”
Section: Dietmentioning
confidence: 99%